Cover Feature: Optimization of Electrode Potential Ranges for Constructing 4.0 V Carbon‐Based Supercapacitors (ChemElectroChem 3/2020). Issue 3 (21st January 2020) - Ye, Meng; Guo, Hongwei; Dou, Qingyun; Guo, Hui; Hou, Ruilin; Guo, Junhong; Yan, Xingbin
Abstract : The Cover Feature depicts supercapacitors based on hierarchically porous carbon electrodes and ionic liquid electrolyte. The mass‐balancing strategy is easy to handle, whereas the pre‐charging strategy can achieve a higher energy density. Consequently, the resultant two supercapacitors are able to operate at the theoretical voltage of 4.0 V along with superior energy densities of 112.33 Wh kg −1 and 132.56 Wh kg −1 . More information can be found in the Article by M. Ye et al. on page 624 in Issue 3, 2020 (DOI: 10.1002/celc.201901922 ).